Too complex to work: A critical assessment of the bail-in tool under the European bank recovery and resolution regime - Tobias Tröger (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
This paper analyzes the bail-in tool under the Bank Recovery and Resolution Directive (BRRD) and predicts that it will not reach its policy objective. To make this argument, this paper first describes the policy rationale that calls for mandatory private sector involvement (PSI). From this analysis, the key features for an effective bail-in tool can be derived. These insights serve as the background to make the case that the European resolution framework is likely ineffective in establishing adequate market discipline through risk-reflecting prices for bank capital. The main reason for this lies in the avoidable embeddedness of the BRRD's bail-in tool in the much broader resolution process, which entails ample discretion of the authorities also in forcing private sector involvement. Moreover, the idea that nearly all positions on the liability side of a bank's balance sheet should be subjected to bail-in is misguided. Instead, a concentration of PSI in instruments that fall under the minimum requirements for own funds and eligible liabilities (MREL) is preferable. Finally, this paper synthesized the prior analysis by putting forward an alternative regulatory approach that seeks to disentangle private sector involvement as a precondition for effective bank-resolution as much as possible form the resolution process as such.
urn:nbn:de:hebis:30:3-438812
Keywords: G01; G18; G21; G28; K22; K23; 330; bail-in; private sector involvement; precautionary recapitalization; cross-border insolvency; market discipline